Reaction of potential guava rootstocks to Meloidogyne enterolobii - Chiamolera, Fernando Marcelo; Martins, Antonio Baldo Geraldo; Soares, Pedro Luiz Martins; Cunha-chiamolera, Tatiana Pagan Loeiro Da (Universidade Federal de Viçosa, 2018)
ABSTRACT Root-knot nematode Meloidogyne enterolobii is the main phytosanitary problem of guava cultivation in Brazil. Among the strategies to manage the problem, the best prospects are in identifying or developing cultivars or rootstocks that are resistant to this nematode. To identify plants with potential as rootstocks for guava, the reaction of araçá (wild guava) to M. enterolobii was assessed in a greenhouse experiment. Seven araçá species were evaluated (Eugenia stipitata, Psidium acutangulum, P. cattleyanum ‘yellow’, P. friedrichsthalianum, P. guajava var. minor, P. guineense, and Psidium sp.). The plants were inoculated with a suspension of 3,000 eggs of M. enterolobii, using eggplant as control treatment. The parameters fresh root mass, number of eggs and second stage juveniles (J2) per root system, the reproduction factor (RF = Pf/Pi), and araçá reaction were determined during the experiment. RF of the araçá species E. stipitata, P. cattleyanum ‘yellow’, and P. friedrichsthalianum was less than one (RP < 1), therefore resistant to M. enterolobii. The araçá trees had good root system development and the susceptible plants showed many root galls, high number of eggs and J2, and Fusarium solani and Rhizoctonia solani root rot. The araçá species, P. cattleyanum ‘yellow’, P. friedrichsthalianum, and E. stipitata are resistant to M. enterolobii and can be tested as potential guava rootstocks.

RESUMO O nematoide das galhas, Meloidogyne enterolobii, é o principal problema fitossanitário para o cultivo da goiabeira. Entre as estratégias para o manejo deste nematoide, as melhores perspectivas estão na identificação ou no desenvolvimento de cultivares ou porta-enxertos resistentes. Buscando elucidar quais plantas poderão ser testadas como porta-enxertos de goiabeira, um experimento foi conduzido em casa de vegetação com o objetivo de avaliar a reação de araçazeiros frente a M. enterolobii. Sete espécies de araçazeiros foram avaliadas (Eugenia stipitata, Psidium acutangulum, P. cattleyanum ‘amarelo’, P. friedrichsthalianum, P. guajava var. minor, P. guineense e Psidium sp.), as quais foram inoculadas com uma suspensão de 3.000 ovos de M. enterolobii, sendo utilizadas plantas de berinjela como tratamento controle. Durante as avaliações, foram determinados a massa fresca de raízes, o número de ovos e juvenis de segundo estádio (J2) por sistema radicular, o fator de reprodução [FR = Pf/Pi] e a reação dos araçazeiros. Os araçazeiros, E. stipitata, P. cattleyanum ‘amarelo’ e P. friedrichsthalianum tiveram fator de reprodução menor que um (FR < 1), sendo, portanto, resistentes a M. enterolobii. Nesses araçazeiros houve bom desenvolvimento do sistema radicular e nas plantas suscetíveis (FR>1) foram observadas muitas galhas, elevado número de ovos e J2 e necroses nas raízes, com a presença de Fusarium solani e Rhizoctonia solani. Os araçazeiros, P. cattleyanum ‘amarelo’, P. friedrichsthalianum e E. stipitata são resistentes ao M. enterolobii e podem ser testados como possíveis porta-enxertos de goiabeira.
Reação de possíveis porta-enxertos de goiabeira a Meloidogyne enterolobii
Keywords: Psidium guajava; araçá species; root-knot nematode; genetic resistance; Psidium guajava; araçazeiros; nematoide das galhas; resistência genética